Kolej Kowary-Kamienna Góra na tle lokalnych linii górskich Dolnego Śląska do 1945 r. - Dominas, Przemysław (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The paper presents the history of Kowary–Kamienna Góra railway in the time of German administration, including problems associated with its construction, technical infrastructure and functioning. This establishment was compared to other similar railway lines in Lower Silesia. The results of the archive queries allow for a conclusion that this railway did not differ from other such ventures within its category
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne